2022
DOI: 10.3390/insects13080719
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Feeding Characteristics in Shaping Gut Microbiota Composition and Function of Ensifera (Orthoptera)

Abstract: Feeding habits were the primary factor affecting the gut bacterial communities in Ensifera. However, the interaction mechanism between the gut microbiota and feeding characteristics is not precisely understood. Here, the gut microbiota of Ensifera with diverse feeding habits was analyzed by shotgun metagenomic sequencing to further clarify the composition and function of the gut microbiota and its relationship with feeding characteristics. Our results indicate that under the influence of feeding habits, the gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that feeding characteristics are the primary factor affecting the structure of the gut bacterial communities of insects [ 36 , 37 ]. The horizontal transmission of food has a significant effect on the bacterial structure of the insect gut, and some bacteria are not able to colonize the body in the absence of external bacterial supplementation, causing changes in the dominant species or core bacterial groups at different life stages [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that feeding characteristics are the primary factor affecting the structure of the gut bacterial communities of insects [ 36 , 37 ]. The horizontal transmission of food has a significant effect on the bacterial structure of the insect gut, and some bacteria are not able to colonize the body in the absence of external bacterial supplementation, causing changes in the dominant species or core bacterial groups at different life stages [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insect gut microbial communities co-evolve with their hosts, enabling insects to adapt to different diets and overcome the limitations of obtaining nutrients from food and countering defensive chemicals ( 3 ). Insect guts commonly harbor bacterial families such as Enterobacteriaceae, Pseudomonadaceae, and Lactobacillaceae, which play vital roles in digestion, immunity, detoxification, and reproduction processes ( 4 6 ). For instance, in Drosophila , Enterobacteriaceae aids in digestion and absorption by degrading carbohydrates in the intestinal tract ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…We previously developed Autometa, an automated binning pipeline that is able to effectively recover genomes from highly convoluted environmental and non-model host-associated microbial communities (3). This tool has seen widespread use in environments ranging from marine, freshwater and terrestrial samples, including corals (4), red algae (5), kinetoplastids (6), deep sea geothermal vents (7)(8)(9), sponges (10)(11)(12), coastal sediments (13), stromatolites (14), seaweeds (15), shipworms (16), plateau lakes (17,18), hot springs (19,20), contaminated rivers (21), beetles (22)(23)(24)(25), Kickxellomycotina fungi (26), Ensifera insects (27), fermented agave (28,29), a marsh orchid rhizobiome (30), domesticated cattle (31,32), mice (33) and human gut (34), periodontal (35) as well as urinary tract (36) microbiomes. As a consequence of Autometa's widespread use, both non-technical and technical researchers alike have communicated their frustrations regarding the ease of installation as well as the efficiency and robustness throughout the various stages of the Autometa workflow.…”
Section: Introductionmentioning
confidence: 99%